Optimization of raw ewes’ milk high-pressure pre-treatment for improved production of raw milk cheese - Inácio, Rita (2022)
Serra da Estrela protected designation of origin (PDO) cheese is manufactured with raw milk from Bordaleira and/or Churra Mondegueira da Serra da Estrela sheep breeds. Several socio-environmental shortcomings have reduced production capacity; hence, treatments that may contribute to its efficient transformation into cheese are welcome. High-pressure processing (HPP) milk pre-treatment may contribute to a cheese yield increment, yet optimization of processing conditions is warranted. An initial wide-scope screening experiment allowed for pinpointing pressure intensity, holding time under pressure and time after HPP as the most important factors influencing curd yield. Based on this, a more targeted screening experiment allowed for selecting the range of experimental conditions to be used for an experimental design study that revealed an HPP treatment at 121 MPa for 30 min as the optimum for milk processing to improve curd yield (>9%) and effectively maintain the beneficial cheese microbiota; the optimum was validated in a final experimental framework.